How Role-Playing Games Have Been Designed for Software Engineering Learning: A Rapid Review - Corrêa, Chessman K. F.; Xexéo, Geraldo (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2025.10057, 2025)
Software developers require both technical and soft skills to deliver high-quality software on time and within budget. As a result, students must acquire these competencies. However, maintaining student motivation and engagement in learning and practice remains a significant challenge. Game-Based Learning (GBL) has emerged as a strategy to help address this issue. This paper presents a rapid review aimed at understanding how role-playing games (RPGs) have been designed to support Software Engineering (SE) education. The reviewed RPGs include both digital and non-digital formats and have been applied to SE as a whole or to specific subtopics. These approaches addressed both hard and soft skills. While game design theories were not employed in all cases, most of the studies were grounded in learning theories.